The development of outcome-based education (OBE)-oriented teaching materials through problem-based and project-based learning for the elementary science education course - Laili Rahmi; Zaka Hadikusuma Ramadan; Ibnu hajar; Ratna Syafitri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop new teaching resources for science education courses in elementary schools that emphasize outcome-based education (OBE) and integrate project-based learning (PjBL) and problem-based learning (PBL) methodologies. This development addresses the need to enhance the quality of OBE-based learning materials, highlighting that traditional teaching resources often fail to meet student expectations. This research focuses on the development and validation phase; the limitation of this research is that it does not include effectiveness testing. Employing the Research and Development (R&D) approach guided by the Borg and Gall framework, the study progressed through structured phases: prototype creation, initial testing, refinement, field implementation, and finalization of the product. Participants in this research included subject matter experts, instructional design specialists, media experts, course instructors, and students from the Elementary School Teacher Education (PGSD) program. Validation results indicated that the developed materials achieved an average feasibility score of 89.81%, placing them within the "highly valid" category. The use of these teaching materials is anticipated to foster students' critical thinking, analytical reasoning, and collaboration skills, aligning with OBE learning outcomes and the objectives of the Merdeka Belajar Kampus Merdeka (MBKM) initiative. The study suggests that future research should further investigate the impact and effectiveness of these materials across broader educational settings.